All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 63883 by mmkkmm000m last updated on 10/Jul/19
∫ln(x)ln(1−x)ln(1−2x)dx
Commented by mathmax by abdo last updated on 12/Jul/19
letA=∫ln(x)ln(1−x)ln(1−2x)dxwehaveln′(1−u)=−11−u=−∑n=0∞un⇒ln(1−u)=−∑n=0∞un+1n+1+c(c=0)=−∑n=1∞unn(∣u∣<1)⇒for∣x∣<12wegetln(1−2x)=−∑n=1∞2nxnnandln(1−x)=−∑n=1∞xnn⇒ln(1−x)ln(1−2x)=(∑n=1∞2nnxn).(∑n=1∞xnn)=∑n=1∞cnxnwithcn=∑i+j=naibj=∑i=1naibn−i=∑i=1n2ii1n−i⇒ln(1−x)ln(1−2x)=∑n=1∞(∑i=1n2ii(n−i))xn⇒∫ln(x)ln(1−x)ln(1−2x)dx=∫lnx(∑n=1∞∑i=1n2ii(n−i))xndx=∑n=1∞∑i=1n2ii(n−i)∫xnln(x)dx+cWn=∫xnln(x)dxbypartsWn=xn+1n+1ln(x)−∫xn+1n+1dxx=xn+1n+1ln(x)−1(n+1)∫xndx=xn+1ln(x)n+1−xn+1(n+1)2⇒∫ln(x)ln(1−x)ln(1−2x)dx=∑n=1∞∑i=1n2ii(n−i)xn+1ln(x)n+1−∑n=1∞∑i=1n2ii(n−i)(n+1)2xn+1+c
Terms of Service
Privacy Policy
Contact: info@tinkutara.com